Implementation of Green Accounting Based on University Social Responsibility - Dwi Suhartini; Tituk Diah Widajantie; Astrini Aning Widoretno; Fajar Nugroho (Nusantara Science and Technology Proceedings, 2020)
University is a contributor to waste from its operational impacts, for this reason, it is obliged to report its activities to protect the environment. This is in line with the achievement of the Sustainable Development Goals in 2030, namely ending poverty, reducing inequality, and protecting the environment. For that, it is very appropriate if all universities in Indonesia implement University social responsibility (USR). The purpose of this study was to examine more deeply the implementation of USR using a literature review approach. This study makes a real contribution in making public policies about the importance of implementing USR in University. For this reason, the research question is the extent to which USR based green accounting is implemented which includes environmental awareness, environmental involvement, environmental reporting, and environmental auditing. The results of the study have proven that the implementation of USR-based green accounting has been carried out by tertiary institutions properly, in real-life lectures (KKN) activities such as conducting training for the community on organic and non-organic waste management and empowering communities around campus. However, the environmental report has not been published properly even though the report has been made. Also, the implementation of environmental audits has not been carried out optimally.